2018
DOI: 10.5539/ibr.v11n2p16
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Critical Success Factors Influence on Critical Delays for Water Infrastructure Construction Projects in the Abu Dhabi emirate Using PLS-SEM Method

Abstract: The objective of this study is to investigate the significance impact of critical success factors on critical delays in the field of water infrastructure construction projects (WICPs) in the Abu Dhabi emirate in particular. Investigation was conducted utilizing quantitative approach by means of questionnaire survey to examine the understanding of professionals engaged in water infrastructure construction towards several critical success factors influencing critical delays. A total of 323 completed responses fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
(61 reference statements)
1
7
0
Order By: Relevance
“…The most important factors of construction projects are their length, importance, operations, density, and priority (Zou et al, 2014;Altarawneh et al, 2018). It should also be noted that construction projects, which can comprise several activities, may operate beyond their contractual deadline (Li et al, 2012;Altarawneh et al, 2018). On the other hand, several studies have discovered that project leader performance can affect development projects (Altarawneh et al, 2018;Rashid et al, 2020).…”
Section: China-pakistan Economic Corridor Project Benchmark Characteristics and China-pakistan Economic Corridor Developmentmentioning
confidence: 99%
See 3 more Smart Citations
“…The most important factors of construction projects are their length, importance, operations, density, and priority (Zou et al, 2014;Altarawneh et al, 2018). It should also be noted that construction projects, which can comprise several activities, may operate beyond their contractual deadline (Li et al, 2012;Altarawneh et al, 2018). On the other hand, several studies have discovered that project leader performance can affect development projects (Altarawneh et al, 2018;Rashid et al, 2020).…”
Section: China-pakistan Economic Corridor Project Benchmark Characteristics and China-pakistan Economic Corridor Developmentmentioning
confidence: 99%
“…It should also be noted that construction projects, which can comprise several activities, may operate beyond their contractual deadline (Li et al, 2012;Altarawneh et al, 2018). On the other hand, several studies have discovered that project leader performance can affect development projects (Altarawneh et al, 2018;Rashid et al, 2020). Research has suggested that if a project has tasks that are common rather than complicated (Gudienė et al, 2013), the project leader will schedule and track project activities.…”
Section: China-pakistan Economic Corridor Project Benchmark Characteristics and China-pakistan Economic Corridor Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is not uncommon to see a construction project failing to achieve its goal within the specified cost, time, and quality. In order to counter the unforeseen delays beforehand the realm of "Project management" is resorted which helps mitigate the delays [37,38].…”
Section: Schedule Delay In Constructionmentioning
confidence: 99%